1998
DOI: 10.1590/s0004-282x1998000400010
|View full text |Cite
|
Sign up to set email alerts
|

Neurocisticercose: contribuição da necrópsia na consolidação da notificação compulsória em Ribeirão Preto-SP, Brazil

Abstract: RESUMO -O presente estudo tem como objetivo a apresentação dos achados de cisticercose nas necrópsias realizadas no Serviço de Patologia do Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto-USP, no período de 1992 a 1997. Das 2522 necrópsias, a neurocisticercose foi detectada em 38 (1,5%) dos casos. Destes, 22 (57,9%) foram diagnosticados apenas na necrópsia enquanto 16 (42,1%) apresentavam exames complementares consistentes com cisticercose. A análise dos prontuários médicos evidenciou que 21 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
8

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
1
24
1
8
Order By: Relevance
“…Cysticercosis prevalence is unknown, because reporting the disease is not officially mandatory. Moreover, various authors agree that there is a lack of knowledge on the factors accounting for the high endemicity of cysticercosis in some regions of the State 4,5,7 . It is reasonable to posit that nonspecific sanitation measures and improved schooling and socioeconomic conditions may have caused this drop in incidence.…”
Section: Number Of Causes Mentioned Per Death Certificatementioning
confidence: 99%
See 2 more Smart Citations
“…Cysticercosis prevalence is unknown, because reporting the disease is not officially mandatory. Moreover, various authors agree that there is a lack of knowledge on the factors accounting for the high endemicity of cysticercosis in some regions of the State 4,5,7 . It is reasonable to posit that nonspecific sanitation measures and improved schooling and socioeconomic conditions may have caused this drop in incidence.…”
Section: Number Of Causes Mentioned Per Death Certificatementioning
confidence: 99%
“…Almost 50,000 deaths attributable to neurocysticercosis occur every year. The severity of cysticercosis can also be illustrated by its case-fatality rate, varying from 16.4% to 25.9% 1,2,3,4,5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em pesquisa realizada próxima à região estudada, encontrou-se um coeficiente de prevalência de neurocisticercose de 67 casos/100.000 habitantes através de notificação compulsória 5 .…”
Section: Introductionunclassified
“…The highest prevalence rates of NC in Brazil has been reported to vary from 4 to 18%, in association with hyperendemic areas of T. solium infestation 6 . However, based upon large series of cases and using various diagnostic methods, several Brazilian authors [7][8][9] have reported a NC prevalence rate of 1-1.5%. It is estimated that there are 50 million carriers of T. solium cysticerci worldwide 10 .…”
mentioning
confidence: 99%